2021
DOI: 10.1021/acsami.1c02314
|View full text |Cite
|
Sign up to set email alerts
|

Bendable BiVO4-Based Photoanodes on a Metal Substrate Realized through Template Engineering for Photoelectrochemical Water Splitting

Abstract: Unlike planar photoelectrodes, bendable and malleable photoelectrodes extend their application to mechanical flexibility beyond conventional rigid structures, which have garnered new attention in the field of photoelectrochemical water splitting. A bendable metal (Hastelloy), which has both bendability and compatibility with various oxide layers, allows high-temperature processes for crystallization; therefore it is far superior as a substrate than a conventional flexible polymer. In this study, we fabricate b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…0.3 V vs the RHE) originates from the trapped photogenerated charges caused by light exposure. 40 We also measured the photocurrent density and the transient curve of 10 nm-thick Fe 2 O 3 with and without a hole scavenger. The Fe 2 O 3 (10 nm)/ BVO/WO 3 /FTO photoanode measured with the hole scavenger shows almost a twice higher photocurrent density compared with the photoanode without the hole scavenger.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…0.3 V vs the RHE) originates from the trapped photogenerated charges caused by light exposure. 40 We also measured the photocurrent density and the transient curve of 10 nm-thick Fe 2 O 3 with and without a hole scavenger. The Fe 2 O 3 (10 nm)/ BVO/WO 3 /FTO photoanode measured with the hole scavenger shows almost a twice higher photocurrent density compared with the photoanode without the hole scavenger.…”
Section: Resultsmentioning
confidence: 99%
“…The photocurrent increase before the onset potential (0 ∼ ca. 0.3 V vs the RHE) originates from the trapped photogenerated charges caused by light exposure . We also measured the photocurrent density and the transient curve of 10 nm-thick Fe 2 O 3 with and without a hole scavenger.…”
Section: Resultsmentioning
confidence: 99%
“…In an interesting study, Lee and coworkers reported the fabrication of bendable BiVO 4 crystalline thin films on a MgO/Y 2 O 3 /Al 2 O 3deposited Hastelloy (M-has) substrate. 293 To reduce the structural mismatch between BiVO 4 and the substrate, the authors also used SrRuO 3 (SRO)/SrTiO 3 (STO) template layers. Furthermore, a WO 3 layer was added between BiVO 4 films and SRO/STO layers to form a type II heterojunction for charge separation and transfer (as shown in Figure 28D,E).…”
Section: Bendable Metal Substratementioning
confidence: 99%
“…(E) Schematic of the bent BVO/WO thin-film photoanode. (F, G) PEC performance comparison of the pristine BVO/ WO and tensile-bent BVO/WO photoanodes.Reproduced with permission: Copyright 2021, American Chemical Society 293.…”
mentioning
confidence: 99%
“…The oxide semiconductor materials such as zinc oxide (ZnO) have attracted considerable research attention owing to their unique photoelectric properties, especially in the field of photoelectrochemistry [1][2][3][4] , and has achieved many research advances in various photoelectric application, including photodetector, semiconductor biosensor and photocatalytic device, etc [5][6][7][8][9] . However, as a wide band gap semiconductor, ZnO (3.37 eV) absorbs 5% of the solar spectrum in ultraviolet (UV) range.…”
Section: Introductionmentioning
confidence: 99%